Pembuatan Indeks Beranotasi Surat Kabar Terbitan Sumatra Barat tentang Kebudayaan Minangkabau - Fahrulrozi, M Ikhsan; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractÂ The library at the Padang City Library and Archives Service is one of the libraries that provides services for users. Index is a tool to retrieve information quickly and accurately, with the index user can easily find information when needed without the need to read the entire contents of newspaper articles. In accordance with the needs of users related to information, we need more complex information tracking tools such as annotated indexes of newspaper articles. One means of tracing information by subject is the subject of Minangkabau culture. Users who need information about Minangkabau culture will find it easier to find that information through an index search tool.Keywords: Annotated Index of Newspapers Published in WestÂ Â